Pengaruh Profitabilitas, Leverage, Dan Likuiditas terhadap Harga Saham Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman di Bursa Efek Indonesia - Sri Ayu Nuramalia Kaharuddin; Yana Fajriah; H. Syamsul Ridjal (STIE AMKOP, 2022)
Abstrak This study aims to examine and analyze the Effect of Profitability, Leverage, and Liquidity on Stock Prices in Manufacturing Companies in the Food and Beverage Sub-Sector on the Indonesia Stock Exchange. Data collection uses secondary data by processing the financial statements of manufacturing companies in the food and beverage sub-sector for the period 2018-2021 using purposive sampling technique with 10 companies so that 40 samples are obtained. The results of these financial statements have been tested for classical assumptions and multiple linear regression tests. The results show that the first hypothesis is accepted because Profitability has a positive and significant effect on Stock Prices, the second and third hypotheses are rejected because Leverage and Liquidity have no significant effect on Stock Prices, and the fourth hypothesis is accepted because Profitability, Leverage, and Liquidity have a significant effect simultaneously on Prices. share. Kata kunci : Profitability, Leverage, Liquidity, Stock Price